Oseltamivir reduces hippocampal abnormal EEG activities after a virus infection (influenza) in isoflurane-anesthetized rats - Cissé Y; Inoue I; Kido H (Dove Medical Press, 2012)
Youssouf Cissé,1 Isao Inoue,2 Hiroshi Kido11Division of Enzyme Chemistry, 2Division of Molecular Neurobiology, Institute for Enzyme Research, University of Tokushima, Tokushima, JapanBackground: Oseltamivir phosphate (OP, Tamiflu®) is a widely used drug in the treatment of influenza with fever. However, case reports have associated OP intake with sudden abnormal behaviors. In rats infected by the influenza A virus (IAV), the electroencephalogram (EEG) displayed abnormal high-voltage amplitudes with spikes and theta oscillations at a core temperature of 39.9°C to 41°C. Until now, there has been no information describing the effect of OP on intact brain hippocampal activity of IAV-infected animals during hyperthermia.Objective: The aim of the present study was to examine the effect of OP on abnormal EEG activities in the hippocampus using the rat model of influenza-associated encephalopathy.Methods: Male Wistar rats aged 3 to 4 weeks were used for the study. Influenza A/WSN/33 strain (1 × 105 plaque forming unit in PBS, 60 µL) was applied intranasally to the rats. To characterize OP effects on the IAV-infected rats, EEG activity was studied more particularly in isoflurane-anesthetized IAV-infected rats during hyperthermia.Results: We found that the hippocampal EEG of the OP-administered (10 mg/kg) IAV-infected rats showed significant reduction of the high-voltage amplitudes and spikes, but the theta oscillations, which had been observed only at >40°C in OP non-administered rats, appeared at 38°C core temperature. Atropine (30 mg/kg) blocked the theta oscillations.Conclusion: Our data suggest that OP efficiently reduces the abnormal EEG activities after IAV infection during hyperthermia. However, OP administration may stimulate ACh release in rats at normal core temperature.Keywords: influenza A virus, oseltamivir, electroencephalogram, slow oscillations, theta oscillations, hippocampus